Screen Culture and Literary Mythology of Mass Consciousness (two “Onegins” – 1999 and 2024) - Sergey N. Ilchenko (Гуманитарный вектор)
The article discusses the practice of promoting the images and meanings of classical works of Russian literature in modern screen culture. The relevance of this topic is connected with the widespread use of images of Russian literature in those samples of screen culture that the modern mass audience is faced with. In the article, the method of comparative analysis will be used as the main research method. The author proposes to compare two cinematic versions of one of the key works of Russian literature - the novel ‘Eugene Onegin’ by A. S. Pushkin. In the course of the analysis, it is proposed to study the circumstances of the creation of both fi lms, the cultural and socio-psychological context of the appearance of screen adaptations, and the general historical background. Particular attention will be paid to the country of origin of each of the fi lms (Great Britain and Russia), which, of course, could not affect the fi nal result. The author examines the adequacy of screen versions, taking into account the existing traditions of fi lm viewing and fi lm perception, determined not only by the practice of the viewers themselves, but also by the dominant information and analytical trends characteristic of mass communication channels, taking into account the circumstances of their functioning in each specifi c, chronological deterministic case. The author paid special attention to the principles of creating both fi lms, the factors that formed the fi nal aesthetic solution of each of the versions - from the selection of actors to the choice of locations and location locations. The article also touches upon the history of cinematic versions of the literary source. The traditions of literary criticism and critical analysis of the original text by A. S. Pushkin in Russian literary criticism are also taken into account. Attention is also paid to the distribution fate of each of the fi lms, since they were created in completely different conditions and in different systems of fi lm production with different cultural traditions necessary for subsequent promotion to audiences.The author comes to the conclusion about the varying degree of aesthetic adequacy of the analyzed phenomena of screen culture to the literary source, when, in his opinion, the approach of British cinematographers is preferable.